2016
DOI: 10.1007/s11751-016-0267-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple osteochondromas (MO) in the forearm: a 12-year single-centre experience

Abstract: Multiple osteochondromas (MO) are a rare autosomal dominant disorder characterized by the presence of osteochondromas located on the long bones and axial skeleton. Patients present with growth disturbances and angular deformities of the long bones as well as limited motion of affected joints. Forearm involvement is found in a considerable number of patients and may vary from the presence of a simple osteochondroma to severe forearm deformities and radial head dislocation. Patients encounter a variety of proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In complex forearm corrections, and here in chronic Monteggia pathology patients, an individualized treatment plan depending onthe deformity, the age ofthe patient, and the status of the radial head and the PRU joint can either lead to a near anatomic reconstruction with good functional result or, in cases of longstanding deformity and established arthrosis, salvage procedures with good pain reduc-tion and functional improvement. Here the complication rate (in the authors' consecutive series) is >10%, comprising nerve injury (under 2%), residual deformity (around 6%), pin-site related infection (3%), reoperation for postoperative ulnar plus deformity, hardware removal, and soft tissue revision [1,3,12,13,21]. All complex corrections, e.g., fixator-based techniques, are prone Fig.…”
Section: Armamentarium and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In complex forearm corrections, and here in chronic Monteggia pathology patients, an individualized treatment plan depending onthe deformity, the age ofthe patient, and the status of the radial head and the PRU joint can either lead to a near anatomic reconstruction with good functional result or, in cases of longstanding deformity and established arthrosis, salvage procedures with good pain reduc-tion and functional improvement. Here the complication rate (in the authors' consecutive series) is >10%, comprising nerve injury (under 2%), residual deformity (around 6%), pin-site related infection (3%), reoperation for postoperative ulnar plus deformity, hardware removal, and soft tissue revision [1,3,12,13,21]. All complex corrections, e.g., fixator-based techniques, are prone Fig.…”
Section: Armamentarium and Resultsmentioning
confidence: 99%
“…Posttraumatic elbow and forearm deformity can occur after either non-operative or operative treatment of acute fractures, as well as following deformity correction surgery (iatrogenic); it presents as impairment of function that is often exacerbated during growth [1]. While the most common deformity at the elbow, varus deformity, was seen for many years as a "purely" cosmetic problem, recent publications and the observation in the authors' multidisciplinary group from Hamburg, Düsseldorf, and Markgröningen, Germany, have shown that longstanding varus deformity of the elbow can lead to ulnar neuritis, medial instability, and functional impairment of the affected upper extremity [3][4][5][6][7]. Nonunion of the radial or ulnar condyle leads to severe arthrosis of the affected elbow joint, resulting in pain, loss of motion, and handicap in daily life and professional activities [8].…”
Section: Examining the Patient Analyzing The Deformity And Informedmentioning
confidence: 99%
See 3 more Smart Citations